"No Regrets" option, corporate governance, and behavior: a mixed method study of stewardship governance in small and medium enterprises - Lumpay, Maricel Due (City of San Fernando, La Union [s.l.], 2022)
From the lenses of owner-managers and their employees, the study identified two categorizations of stewardship governance, one that is structured and driven by legal compliance and an altruistic one founded in ethics. Stewardship governance is the goal that fills the gap for SMEs' commitment to 'no regrets" sustainability initiatives and inclusiveness. Using mixed-method approach , which a concurrent explanatory triangulation of a qualitative core and quantitative supplemental component of 14 SMEs, the study investigated owner-managers' views on stewardship governance, understanding the coexistence of governance influence on stewardship behavior and stewardship as underlying ethics of governance to facilitate "no regrets" sustainability initiatives. Results showed that stewardship governance, which is the integration of governance and behavior in firms, may influence and drive agent behavior to practice stewardship and act on "no regrets" initiatives an extra ordinary times such as natural disasters. Similarly, a steward behavior that practices agency governance may demonstrate stewardship actions through compliance with legal or mandated programs, given the firms' limited resources. Moreover, the study revealed that either agency or stewardship's governance does not guarantee positive financial performance. Instead, the behavior of the principal, either as agent or steward, drives the firm to better performance.
St. Thomas Moore College, Angeles City, Pampanga
Keywords: Business Enterprises